1986
DOI: 10.1007/bf00178518
|View full text |Cite
|
Sign up to set email alerts
|

A late-appearing benzodiazepine-induced hypoactivity that is not reversed by a receptor antagonist

Abstract: The activity of rats in a holeboard test is reduced 30, 90, and 240 min after treatment with a single dose of lorazepam. The administration of a benzodiazepine antagonist (RO 15-1788) 20 min before the holeboard test (i.e., 10, 70, or 220 min after lorazepam administration) reverses the hypoactivity of animals tested 30 min after treatment with lorazepam, partially reverses the hypoactivity of animals tested 90 min after receiving lorazepam, but is without effect on the hypoactivity observed 240 min after trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1986
1986
1989
1989

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The early occurring decreases in expioratory head-dipping and motor activity were reversed by flumazeniI, and this is in accord with all previous studies (e.g., Hunkeler et al 1981;Bonnetti et al 1982;Lister and File 1986) and suggests that these behavioural changes are mediated by the benzodiazepine receptors. However, the interest in the present study was whether the late-appearing behaviourai changes were benzodiazepine receptor mediated.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The early occurring decreases in expioratory head-dipping and motor activity were reversed by flumazeniI, and this is in accord with all previous studies (e.g., Hunkeler et al 1981;Bonnetti et al 1982;Lister and File 1986) and suggests that these behavioural changes are mediated by the benzodiazepine receptors. However, the interest in the present study was whether the late-appearing behaviourai changes were benzodiazepine receptor mediated.…”
Section: Discussionsupporting
confidence: 85%
“…For example, the anticonvulsant effect of oxazepam in mice persisted at an almost constant level from 1 to 7.5 h after oral administration, and for two different strains of mice there was a good within-strain correlation between anticonwllsant effect and receptor occupancy (Wilks et al 1987). In the rat, a lateappearing hypoactivity has been found 4 h after lorazepam administration, but this did not seem to be mediated by the benzodiazepine receptor because it was not reversed by flumazenil, the benzodiazepine antagonist (Lister and File 1986). It was suggested that the hypoactivity was triggered by an initial action at the benzodiazepine receptors that then triggered changes in neurochemical pathways downstream from the benzodiazepine receptors.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Following 7 days of administration of flurazepam (40 mg/kg) mice had a lowered seizure threshold 24 hours later, and this threshold was not modified by administration of the benzodiazepine receptor antagonist Ro 15-1788 (Little et al 1984). Both mice and rats showed a withdrawal response several hours after lorazepam, indicated by a reduction in seizure threshold, hyperactivity and changes in exploratory head-dipping; none of these behaviours was modified by the administration of Ro 15-1788 (Lister & File, 1986;Lister & Nutt, 1986;Wilks & File, unpublished). These studies suggest that an increase in an endogenous inverse-agonist-like ligand is not responsible for withdrawal responses and, furthermore, they demonstrate that it is possible to see a withdrawal response after a single dose of lorazepam.…”
Section: Dependence: Animal Studiesmentioning
confidence: 99%